Títulos verdes e a qualidade da informação contábil - Franco, Mineia Cristina (2024)
The aim of this study is to investigate the relationship between green bonds and the Quality of Accounting Information (QAI) and its determinants in non-financial issuing companies in Latin American (LA) countries from 2017 to 2022. The thesis is that the issuance of green bonds can contribute to improving the quality of the accounting information disclosed. To achieve this objective, we investigated the factors that may be associated with QAI and the issuance of green bonds. We selected 39 green bond issuing companies and 80 non-issuing companies in Latin America. Discretionary accruals were analyzed individually as a proxy for Earnings Management (EM) to determine QAI and the factors that may be associated with QAI and the issuance of green bonds, such as: corporate governance through the characteristics of the board of directors; auditing by big fours; shareholder concentration; institutional investors; internationalization of companies; and voluntary disclosure. The analyses to achieve the proposed objective were based on descriptive statistics, Student's t-test, chi-square test, simple linear regression and logistic regression, considering the two groups of companies analyzed. The results show that factors such as corporate governance, auditing, institutional investors and the internationalization of companies were significant, showing both a relationship with earnings management and an association with the issue of green bonds. Shareholder concentration was only significant when considering factors that could be related to EM. The disclosure variable was not statistically significant when the relationship with EM was observed, but it was statistically significant when associated with the issue of green bonds. Shareholder concentration was not associated with the issue of green bonds. There was also a positive relationship between EM and the issue of green bonds; in other words, for each unit of EM there is a probability of issuing green bonds of around 2.773 units. Therefore, there is evidence that companies that manage their results tend to issue more green bonds and it can be inferred that there may be a practice of greenwashing. The study also shows that the disclosure of information regarding sustainability and the post-issue reporting of bonds need to be improved in the context of the companies analyzed. These results contribute to the literature on green bonds and QAI, identifying that corporate reports, according to legitimacy theory, have not fulfilled their role as social, political and economic documents in order to transmit relevant information to their users, legitimizing their actions in the face of deficiencies in the post-issuance reporting of green bonds and disclosure of information regarding sustainability. The findings can provide important information for regulators to increasingly improve current standards in order to expand the green bond market and establish investor confidence in this financial tool.